Effects of diethyl aminoethyl hexanoate (DA‐6) on the growth and cadmium accumulation of tomato seedlings. Issue 4 (18th February 2021) - Dong, Yiping; Liang, Le; Lin, Lijin; Li, Huanxiu; Liao, Ming'An; Sun, Guochao; Liang, Dong; Xia, Hui; Wang, Jin; Wang, Xun; Tu, Lihua; Tang, Yi
Abstract: Diethyl aminoethyl hexanoate (DA‐6) can lessen the effects of cadmium (Cd) toxicity on some plants. A pot experiment was conducted to examine the impact of different DA‐6 concentrations (0, 10, 20, 30, and 40 mg/L) on growth and Cd accumulation of tomato seedlings. A DA‐6 concentration of 10 mg/L increased the biomass of roots, stems, leaves, and shoots, while the other concentrations either had no significant effects or inhibited the growth of tomato seedlings. Concentrations 10 and 20 mg/L of DA‐6 increased the chlorophyll b and total chlorophyll contents, and the activities of superoxide dismutase and peroxidase. All the four tested concentrations of DA‐6 reduced catalase activity and increased the soluble protein content. Importantly, all tested DA‐6 concentrations decreased the Cd content of tomato seedling roots, and increased in the Cd contents of stems, leaves, and shoots. While 10 mg/L DA‐6 did not significantly affect the translocation factor of tomato seedlings, the other tested DA‐6 concentrations enhanced the translocation factor. Therefore, 10 mg/L DA‐6 could significantly promote the growth of tomato, but all the tested concentrations of DA‐6 could also promote the uptake of Cd in tomato shoots, which could impede the safe production of tomatoes in Cd‐contaminated soils.